KEDUDUKAN HUKUM PERAWAT DALAM MELAKSANAKAN TINDAKAN MEDIS SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 38 TAHUN 2014 TENTANG KEPERAWATAN - Hermana, Maman (Tadulako Master Law Journal, 2021)
This research uses normative or doctrinal legal research with the research approach used is statute approach and historical approach. The statute approach is carried out by examining all laws and regulations relating to the legal issues being addressed. Historical approach is carried out by examining the background of what is learned and the development of arrangements regarding the issues at hand, this action is needed when researchers really want to uncover philosophical thoughts and mindsets that give birth to something that is being studied, which has relevance to the present. The results showed that the implementation of medical actions by nurses, legally have been in accordance with statutory regulations, and do not violate the provisions contained in normative instruments of medicine and nursing, the nursing profession has a legal position carrying out medical actions which must be in accordance with the type of nurse. In the implementation of medical actions performed by nurses who are not in accordance with the type, to this matter has consequences for accountability both criminal, civil and administrative law.